Knowledge, attitude and practice of parents regarding antibiotic use in children - Shamshu, Rasheena; Sudhir, Shyam; Nuwera, Haleema (International Journal of Contemporary Pediatrics, 2019)
Background: Antibiotic resistance has become an emerging issue worldwide due to the rampant and excessive use of antibiotics for any and every condition. At present, antibiotics are the most commonly sold drugs in the developing countries which have been the cause for escalation of antibiotic resistance. Lack of knowledge, awareness and practice among parents regarding antibiotics use is the most important cause for antibiotic misuse. Methods: Cross sectional hospital based questionnaire study conducted among 200 parents of children attending the outpatient or inpatient department at Yenepoya Medical College Hospital, Mangalore; using personal interview method. Parents were asked to answer the statements on a 5-point Likert scale (“strongly agree”, “agree”, “uncertain”, “disagree”, “strongly disagree” or “never”, “sometimes”, “often”, “most of the time”, “always”). Statistical Package of social science (SPSS) software was used for analysis of data. Results: Out of the 200 parent’s majority of the respondents (69%) were mothers. There was very little difference in percentage of respondents that disagreed with notion that antibiotics must be administered in any case of fever (43.3%). 42.3% mentioned that antibiotics were always necessary in ARI. Most common symptoms to visit pediatrician included cough (23.4%), followed by ear pain (18.1%) and nasal discharge (12.9%). 17.5% of parents never questioned the pediatricians if antibiotic administration was necessary and more than 2/3rd of the parents declared that pediatricians provided sufficient information regarding diagnosis and therapy. Conclusions: Majority of parents admitted to self-administration of antibiotics. There is a need of intervention to increase awareness regarding judicious use of antibiotics and to check un-prescribed dispensing of antibiotics. Strategies for effective communication with patients and prudent prescription of antibiotics should be included in physician education to ensure patients’ adherence to advice and consequently to reduce self-medication with antibiotics.